(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the structure of police officers working in the People’s Commissariat of Internal Affairs, which was reorganized after the formation of the Uzbek SSR, including the central structure of the internal affairs system and the national structure of senior and ordinary officers in the regions on the basis of primary archival documents